DESIGNING THE STRUCTURAL CONCEPT OF ESTIMATING THE INTERNATIONAL POSITION OF UKRAINE IN THE WORLD CONTEXT OF STATE FINANCIAL AND ECONOMIC SUPPORT TO THE AGRICULTURAL SECTOR - T. О. Kharchenko (Pressing Problems of Public Administration, 2022)
The article studies the problems of state financial and economic support to the agricultural sector in the world context and substantiates the structural concept of assessing the international position of Ukraine. It is confirmed that there is a connection between the annual values of indicators of total state support for the agricultural sector, support for producers and support for consumers and the international rating position of Ukraine.In the world context the ratings of countries are calculated on indicators of state financial and economic support to the agricultural sector: total estimate of support for the agricultural sector (TSE); producer support estimate (PSE) consumer support estimate (CSE); general service support estimate (GSSE). The international position of Ukraine in terms of ratings is determined, which is radically lower compared to the overall indicator of OECD member states and EU member states. It was confirmed that the dynamics of the ratings of Ukraine in the world context is insignificant, the variability is determined at the level of the 22nd – 24th place in terms of indicators of total estimate of support for the agricultural sector, estimate of support for producers and estimate of consumer support. The dynamics of the decrease in the gap of annual indicators of support for producers and consumers of the agricultural sector in Ukraine since 2018 has been determined. The best position of Ukraine in the international rating is confirmed by the indicator of estimate of general support for services.The analysis was the basis for designing the structural concept of estimating the international position of Ukraine in terms of state support trends for the financial and economic mechanism of state regulation of the development of the agricultural sector, the advantages of which are: determining the position of Ukraine in the world context in terms of state support trends for the agricultural sector; establishment of the level of connection of annual values of indicators of state financial and economic support to the agricultural sector; forming a comparative characteristic of the position of Ukraine to the overall indicator of the EU member states.The calculations confirmed the need to review the directions of state support for the mechanisms of state regulation of sustainable development of the agricultural sector for adaptation to European practices. It was established that within the framework of the implementation of state policy in terms of the development of support measures in the EU countries, seven categories of measures were introduced, among them: sector-wide and institutional measures; information and coordination measures; trade and commodity flow measures; labor measures; support for agriculture and food; general support; food aid and consumer support. It is determined that in the EU countries, the impact of economic cuts on food spending was mitigated thanks to government support, which partially compensated the loss of income, and the reduction in total income led to the maximum direction of food spending. The implementation of this approach confirmed the hypothesis that government support ensured the sustainability of food systems.